Environmental Impact Analysis in the Cement Industry with Life Cycle Assessment Approach - Rika Chairani; Aulia Risky Adinda; Dennis Fillipi; Muhamad Jatmoko; I Wayan Koko Suryawan (Politeknik Sukabumi, 2021)
The cement industry is one type of industry that has implications for the emergence of environmental pollution problems and a decrease in environmental quality due to dust pollution. The cement industry can also increase air temperature and noise in operational activities by using machines. In addition, the impact of the cement industry is the decline in the quality of soil fertility due to clay mining. Thus, an analytical study is needed that can be used as one of the policy bases in the operational process of the cement industry. This study aims to conduct an analysis of environmental loads at each stage in the product life cycle, make decisions to identify environmental loads, and evaluate the environmental impact of a product that plays an important role in sustainable development. This method is known as Life Cycle Assessment (LCA). In this study, the boundary system used is cradle to gate with a three-scenario approach. The first uses 100% coal fuel, the second uses 90% coal fuel, and the third uses 10% rice husk biomass. Then the analysis was carried out using the OpenLCA software. The results of the analysis showed that the most significant emission load was carbon dioxide of 1229.31 kg CO2eq. The third scenario produces the lowest carbon dioxide emission load compared to other methods of 849.1 kg.